2018
DOI: 10.1590/1678-4766e2018007
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and reproductive biology of Haemulopsis corvinaeformis (Perciformes, Haemulidae) in the south coast of Pernambuco, northeastern Brazil

Abstract: Roughneck Grunt (Haemulopsis corvinaeformis Steindachner, 1868) is the second most important species caught as bycatch of the shrimp fishery in Pernambuco, Northeastern Brazil. However, the population dynamic of this species is poorly known in the region. The aim of this study was to describe aspects of the population structure and reproductive biology of the H. corvinaeformis, providing important information for the development of sustainable management practices. Specimens were collected monthly from August … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The CCRF recommends that the entire catch should be managed in an ecologically sustainable manner; thus, a regulation for this area should be established considering the main species involved (target and bycatch). Previous studies in the region have shown that the bulk of the catch of the shrimp fishery in Pernambuco shares the same feeding ground and season of reproduction (e.g., between October and March) (Lopes et al 2014, 2017, 2018, Silva Júnior et al 2015, Eduardo et al 2018b) and a closed season could be established during the austral summer. In addition, the application of BRD (e.g., fisheye, grid and square mesh) used to exclude fish and other small bycatch from the trawl (Broadhurst 2000, Eayrs 2007, Larsen et al 2017) might be a good conservation tool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CCRF recommends that the entire catch should be managed in an ecologically sustainable manner; thus, a regulation for this area should be established considering the main species involved (target and bycatch). Previous studies in the region have shown that the bulk of the catch of the shrimp fishery in Pernambuco shares the same feeding ground and season of reproduction (e.g., between October and March) (Lopes et al 2014, 2017, 2018, Silva Júnior et al 2015, Eduardo et al 2018b) and a closed season could be established during the austral summer. In addition, the application of BRD (e.g., fisheye, grid and square mesh) used to exclude fish and other small bycatch from the trawl (Broadhurst 2000, Eayrs 2007, Larsen et al 2017) might be a good conservation tool.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the trawling bycatch is mainly composed of small individuals, usually juveniles (Silva Júnior et al 2015). However, for C. nobilis, a higher proportion of individuals above the L 50 value were found, thus the majority of the harvested individuals might have been able to reproduce and contribute to population renewal (Eduardo et al 2018b). This represents a good indicator of the sustainability of the stock.…”
Section: Discussionmentioning
confidence: 99%
“…LWR is an important aspect linked to the biology and ecology of fish species, as it assists in the characterization of fish stocks and allows for the establishment of regulations for the management of these natural resources (Lima et al, 2017). Moreover, it has been used to compare species from different regions and environments, seeking to associate changes in body shape and weight with different situations such as growth, reproduction, and anthropogenic impacts (Eduardo et al, 2018; Froese, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Similar average lengths of L50s have been described in females of other species belonging to the Haemulidae family, such as Plectorhinchus gaterinus, with 23 cm (Amin et al, 2019) or Haemulon plumierii with 21.4 cm (Hoffmann et al, 2017). However, substantially smaller L50s are described in other species of this family, such as Haemulopsis corvinaeformis, H. aurolineatum, and H. squamipinna (Eduardo et al, 2018;Cardoso De Melo et al, 2020). Although the L50 provides substantial information in management the stock of wild populations.…”
Section: Discussionmentioning
confidence: 99%